Lastvine– an eneolithic site in Benkovac (Archaeologia Adriatica, 2018)
The papers deals with the results of the excavations conducted in 2009/2010 at the Eneolithic site of Lastvine in Benkovac near Zadar. On the basis of typological and stylistic characteristics of pottery that makes the most abundant group of archaeological finds, the site can be ascribed to the Early Eneolithic period with certainty and associated with a number of synchronous cave sites in the wider region of the eastern Adriatic and its hinterland whose main characteristic is channelled pottery. However as opposed to these sites, Lastvine is the first open-air site, and the same time the first single-layered settlement with this type of pottery. Furthermore there are certain differences in the technique of this ornament execution.